Fostering creativity and entrepreneurship skills in the context of Malaysia MADANI - Jafni , Nurul Huda; Wahab , Samsudin; Khalid , Nor Aminin; Ghazali , Jafni (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the role of arts and crafts pop-up events in fostering creativity and entrepreneurship skills among tertiary students, within the framework of the Malaysia MADANI initiative. Using qualitative methods, including semi-structured interviews with students who have organized such events, the research explores how these experiences empower students to enhance their creative problem-solving abilities, develop entrepreneurial skills, and engage with diverse audiences. The study highlights the significance of creating conducive learning environments, integrating technology, and promoting inclusivity. It also underscores the importance of feedback mechanisms and reflective practices in strengthening both creative and entrepreneurial outcomes. The findings suggest that these events offer students valuable practical experience, helping them build confidence, improve social skills, and gain market exposure, all of which contribute to their professional development. Based on these insights, the research proposes recommendations for universities to further cultivate creativity and entrepreneurship through structured initiatives, regular pop-up events, and support systems, including mentorship and digital marketing training